Capital Mobility and Monetary Policy in Colombia. (IMF Working Papers; Working Paper ;, 1988)
This paper estimates a model of financial markets in Colombia to examine: 1) the authorities' control over domestic interest rates and the money stock; and 2) the effects of the crawling peg exchange rate policy on exchange rate expectations and domestic interest rates. The authorities appeared to possess some control over the money stock in the short run, mostly because of the existence of capital controls, but most of this control was eroded once asset demands adjust to their desired banks. The expected rate of depreciation is not closely linked to the crawling peg.